Extraction and Purification of Vibrio Cholerae Enterotoxin and Study its Cytopathic Effect on Some Mice Organs - Abu-Resha, Rasmyia (Iraqi Journal of Science, 2023)
Vibrio cholerae enterotoxin was extracted by cooling centrifugation and filtrationwith milipore filter (0.22um) and was purified by using Sephacryl –S- 6 gelfiltration,the content of protein was estimated . The results showed proteinconcentration was 28.5 microgram/ml,the present of enterotoxin was detected byinfant suckling mouse method..The cytopathic effect of enterotoxin was studied by injecting a number of mice withpurified enterotoxin, It was found caused shortening the villi of the intestine atconcentration 55 and 45 ug /ml of purified enterotoxin, while the effect on livershowed degenerative change with necrosis at 55 ug/ml of enterotoxin and causednecrosis and infiltration of inflammatory cells at 45 ug /ml, the effect on spleentissue was represented by widening of white pulp, and reduction or disappearance ofred pulp also inflammatory cells wre found i.e. lymphocyte and hypoplasia of whitepulp at the two concentrations of the enterotoxin .